The life and times of germanium and tin complexes ligated by amidinates and guanidinates and exploratory studies in the use of these ligands in the formation of iron complexes. - Foley, Stephen R. (University of Ottawa (Canada), 2000)
The overall objectives in the creation of this work were to investigate the structure and reactivity of the group 14 elements germanium and tin supported by amidinates and guanidinates. Chapter One outlines features of the supporting ligation used throughout the thesis. Chapter Two describes the first characterized amidinate complexes of Ge using alkylamidinates as ancillary ligands. Chapter Three represents the first comprehensive study of a heteronuclear intermetal two-electron sulfur atom transfer between Sn and Ge. Complete sulfur atom exchange between amidinate complexes of tin and germanium was achieved through the reaction of (CyNC(tBu)NCy) 2Sn=S with (CyNC(tBu)NCy)2Ge to form the corresponding germanium sulfide (Ge=S) and stannylene. Chapter Four is concerned with the cleavage of chalcogen-chalcogen bonds as routes to the formation of rare chalcogenolates of tin and germanium. Unusual cyclic tin tetrasulfido complexes {(CyNC(R)NCy)[N(SiMe3 )2]}MS4 (M = Sn, R = Me, tBu; M = Ge, R = Me) were prepared by the reaction of elemental sulfur with the divalent group 14 starting materials [CyNC(R)NCy]M[N(SiMe3)2] (M = Sn, R = Me, tBu; M = Ge, R = Me). In Chapter Five mixed amidinato amido complexes [Me 3SiNC(tBu)NSiMe3]M[N(SiMe 3)2] (M = Sn, Ge) were prepared by the reaction of [Me 3SiNC(tBu)NSiMe3]Li with SnCl2 and GeCl2(dioxane) in ether. The N(SiMe3)2 ligand in these compounds is derived from the rearrangement of the [Me 3SiNC(tBu)NSiMe3]- anion with extrusion of tBuCN. The focus of Chapter Six is on the catalytic cyclotrimerization of isocyanates to perhydro-1,3,5-triazine-2,4,6-triones (isocyanurates) at room temperature. In Chapter Seven, we investigate the use of monoanionic N,N',N″-trisubstituted guanidinates as well as the anion of 1,3,4,6,7,8-hexahydro-2H-pyramido[1,2-a]pyramidine (Hhpp) in the formation of both Sn(II) and Sn(IV) complexes. Chapter Eight deals with investigations into the formation of amidinate and guanidinate complexes of both Fe(II) and Fe(III). Presented in this Chapter are results regarding the use of N, N'-dicyclohexylformamidinate as a ligand with Fe(II) to yield Fe4(mu4-O)(mu-Br) 2(mu-CyNCHNCy)4. (Abstract shortened by UMI.)
Keywords: Chemistry, Inorganic.